ANALISIS USAHA TANI TEBU DI KECAMATAN BAMBANGLIPURO KABUPATEN BANTUL DAERAH ISTIMEWA YOGYAKARTA - Baren Puspita (Jurnal Magrobis, 2018)
Analysis on sugarcane farming in Bambanglipuro district, Bantul regency, special regency of Yogyakarta has been done to the difference of farming system and to analyze more profitable sugarcane farming between Joint Venture Sugarcane Society (TR.KSU), Partnership Sugarcane Society (TR.KMT), and Independent Sugarcane Society (TR. MAN) farmers.The basic method used is descriptive method and analysis so the analysis on sugarcane farming is worth the effort. Sampling location is at Bambanglipuro district, Bantul Regency with 60 samples taken consisting of 20 Joint Venture Sugarcane Society (TR.KSU) farmers, 20 Partnership Sugarcane Society (TR.KMT) farmers, and 20 Independent Sugarcane Society (TR. MAN) farmers. The result of the research shows that Venture Sugarcane Society (TR.KSU) farmers make profit Rp. 19.180.112/Ha on PC and Rp. 15.531.800/Ha on RC. Partnership Sugarcane Society (TR.KMT) farmers make profit Rp. 18.911.388/Ha on PC and Rp. 15.419.800/Ha on RC, and Independent Sugarcane Society (TR. MAN) farmers make profit Rp 22.983.188/Ha on PC and Rp. 17.985.710/Ha on RC.Value of R/C ratio sugarcane farming per Ha for TR.KSU, TR.KMT, and TR.MAN farmers is more than one. This shows that either PC or RC sugarcane farming is worth the effort.Keywords: Sugarcane farming analysis, society’s sugarcane, partnership, farming suitability